Architectures of Thought - Georgios Tsagdis (Footprint)
The present essay advances Stiegler’s neganthropological project by supplementing its genetic structural framework with a metabolic plane of analysis. Neganthropology demands the creation of technologies (exosomatic tertiary inscriptions) that arrest and reconfigure entropic flow, enabling thus collective and personal individuation as well as the diversification of noetic life. All life however must live in and through the ‘now’, which it transforms. This ephemeral yet general metabolic operation of life constitutes the minimal negentropic unit that can be maintained, a ‘now’ that neganthropology must attend to. To do so, technology, life and thought must be examined together, none being elevated to the status of a model for the other two. In attempting a non-hierarchic configuration of the three, the essay proposes a new architecture.